Liposomes in Active, Passive and Acoustically-Triggered Drug Delivery - Al Basha, Sara (2019)
Cancer has become one of the most deadly noncommunicable diseases globally. Several modalities used to treat cancer patients exist today yet many have failed to prove high efficacy with low side effects. The most common example of such modalities is the use of chemotherapeutic drugs to treat cancerous cells and deter their uncontrolled proliferation. In addition to the destruction of cancerous tissues, chemotherapy destroys healthy tissues as it lacks the specificity to annihilate cancerous cells only and preferentially, which result in adverse side effects including nausea, hair fall and myocardial infarction. To prevent the side effects of non-selective chemotherapy, cancer therapy research has been focused on the implementation of nanocarrier systems that act as vehicles to encapsulate drugs and selectively transport their agent to the tumor site. In this paper, we shed light on liposomes along with three anticancer drug delivery approaches: passive, active and ultrasound-triggered drug delivery.